Combinatorial suicide gene strategies for the safety of cell therapies - Falcon, Corey; Smith, Lauren; Al-Obaidi, Mustafa; Abu Zaanona, Mohammed; Purvis, Katelyn; Minagawa, Kentaro; Athar, Mohammad; Salzman, Donna; Bhatia, Ravi; Goldman, Frederick; Di Stasi, Antonio (Frontiers in Immunology, 2022)
Gene-modified cellular therapies carry inherent risks of severe and potentially fatal adverse events, including the expansion of alloreactive cells or malignant transformation due to insertional mutagenesis. Strategies to mitigate uncontrolled proliferation of gene-modified cells include co-transfection of a suicide gene, such as the inducible caspase 9 safety switch (ΔiC9). However, the activation of the ΔiC9 fails to completely eliminate all gene-modified cells. Therefore, we tested a two suicide gene system used independently or together, with the goal of complete cell elimination. The first approach combined the ΔiC9 with an inducible caspase 8, ΔiC8, which lacks the endogenous prodomain. The rationale was to use a second caspase with an alternative and complementary mechanism of action. Jurkat cells co-transduced to co-express the ΔiC8, activatable by a BB homodimerizer, and the ΔiC9 activatable by the rapamycin analog sirolimus were used in a model to estimate the degree of inducible cell elimination. We found that both agents could activate each caspase independently, with enhanced elimination of gene-modified cells when both systems were activated simultaneously. A second approach was employed in parallel, combining the ΔiC9 with the RQR8 compact suicide gene. RQR8 incorporates a CD20 mimotope, targeted by the anti-CD20 monoclonal antibody rituxan, and the QBend10, a ΔCD34 selectable marker. Likewise, enhanced cell elimination was observed when both systems were activated together. A dose-titration effect was also noted utilizing the BB homodimerizer, whereas sirolimus remained very potent at minimal concentrations. Further in vivo studies are needed to validate these novel combination systems, which may play a role in future cancer therapies or regenerative medicine.